Redesign Road Project Using Critical Chain Project Management Method and Crashing Method - Arif Budi Sulistyo; Ilpan Ilpan; Afni Khadijah (OPSI, 2021)
Construction of the Provincial road project from Parigi to Sukamanah is carried out by PT. Jaya Madiri Konsulindo as consultant and PT. Karya Tunas Mandiri Persada as contractor. The problem of the construction project is implementation duration does not match to previous planning which results delay in completion time. It is necessary to re-plan the project in order to get either optimal time or cost. The purpose of this research is to find out the critical work path using critical chain project managemet method by utilizing microsoft project software and optimization of project time and cost using crashing method with alterative increase of working hours (overtime) and addition of labor. The research’ scope is limited on labor cost only. Based on the results of the study obtained that initial labor wage cost is IDR 585,025,000.00 with a working duration of 154 days, and results of the alterative crashing  method is lower with labor wage cost IDR 576,750,000.00. It could save cost about IDR 8,275,000.00 with duration of work 150 days or earlier 4 days from the initial duration.